Undermined by Adverse Selection: Australia's Direct Action Abatement Subsidies1. Issue 3 (13th May 2016) - Burke, Paul J.
Abstract : This paper examines the economic challenges faced by Australia's Direct Action abatement subsidy scheme. Introduced in 2014, the scheme operates by reverse auction, funding projects voluntarily proposed by the private sector. Because the Government cannot know true project counterfactuals, the lowest auction bids are likely to often be non‐additional "anyway" projects. The scheme is hence likely to exhibit a systematic skew towards low‐quality abatement. The paper presents a model of the adverse selection problem and describes the early experience with Direct Action. A discussion of a way forward is also provided.